OPTIMALISASI MANAJEMEN KEUANGAN UMKM UNTUK MENINGKATKAN KEBERLANJUTAN USAHA MELALUI PELATIHAN LAPORAN KEUANGAN SEDERHANA DI LUBUK GADANG, KABUPATEN SOLOK SELATAN - Yefri Reswita; Tilawatil Ciseta Yoda; Nanda Nanda; Darman Darman; Syaiful Syaiful; Silvy Astari (Komunitas Manajemen Kompetitif, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting the local economy in Pauh District, Padang City, as a source of income, job creators, and drivers of the local economy. However, the development of MSMEs still faces obstacles in marketing management, particularly weak promotional skills and a limited understanding of consumer behavior. Most businesses still employ conventional marketing strategies without analyzing customer needs, preferences, and behavior patterns. As a result, promotions are poorly targeted and unable to optimally enhance product competitiveness. Limited marketing literacy and a lack of mentoring also prevent MSMEs from evaluating the effectiveness of their promotional strategies. This community service program aims to strengthen MSME marketing management through training on promotions and consumer behavior analysis. Activities are implemented using a participatory and applied approach through training, discussions, and direct mentoring. Materials cover marketing management concepts, effective promotional techniques, understanding consumer behavior, and simple analysis of customer needs. The expected outcome is an increased capacity of MSMEs in designing consumer-based promotions, thereby increasing sales, competitiveness, and sustaining business sustainability